New challanges of Laboratory Medicine due to population aging. - Dayamí García Torres; Pedro Sánchez Frenes (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Population aging implies impacting consequences for the society and the health system. Laboratory Medicine as part of it, is affected in its three phases: Preanalytical, analytical and postanalytical. This is a serious problem to perform these analysis correctly because of the elderly multimorbidity so as the difficulty to comply with some requierements for the dignosis due to age ( certain dietary limitations). Undoubtely demographic aging brings about new challanges for the laboratory medical services. The present work shows the effects of this phenomenun for the health system and proposes solutions to mitigate its consquences.